Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan Augmented Reality Pada Materi Bangun Ruang Sisi Lengkung - Fahmi, Syariful; Noviani, Dewi Astrida (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2021)
This study aims to develop an android-based mathematics learning media using augmented reality on curved side space, and to find out the feasibility of android-based mathematics learning media using augmented reality on curved side space material. This research is a development research that uses the ADDIE development model. The subjects in this study were students of SMP IT Bustanul 'Ulum class IX, material experts, and media experts. Based on the research that has been done, the results of the feasibility of learning media from material experts are obtained by a percentage of 96.88% which is included in the very feasible criteria, from the media experts a percentage of 91.67% is obtained which is included in the very feasible criteria, from the student responses the percentage is obtained of 84.67% which is included in the very feasible criteria, and from the combined feasibility calculation, a percentage of 91.07% is obtained which is included in the very feasible criteria. Based on the results of the assessment, the android-based mathematics learning media using augmented reality on the curved side space material is declared very feasible to be used as a learning medium in the learning process.